2016
DOI: 10.5961/jhes.2016.156
|View full text |Cite
|
Sign up to set email alerts
|

Employment and first year experience of beginner primary school teachers at private educational institutions

Abstract: In this study to demonstrate primary school teachers' employment process and their first year teaching in private educational organizations is aimed. The major employer of primary school teachers is public schools that are funded by state. There will be a gap between grade inflation and employment rate when all of the teacher candidates claim to be appointed to public schools. Hence private educational organizations provide alternative career opportunities for teacher candidates. Qualitative methods will be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The role of educational leaders in schools is crucial in ensuring meaningful outcomes for all students including those with special needs. The literature related to management of schools has shown that still much effort is needed in developing the strategic skills necessary to provide critical needs for students with disabilities (Okut ve Ontaş, 2015;Ontaş, 2016). Research suggests that one of the strategies that makes inclusion successful is a commitment to a set of core school values by teachers and administrators (Scruggs & Mastropieri, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The role of educational leaders in schools is crucial in ensuring meaningful outcomes for all students including those with special needs. The literature related to management of schools has shown that still much effort is needed in developing the strategic skills necessary to provide critical needs for students with disabilities (Okut ve Ontaş, 2015;Ontaş, 2016). Research suggests that one of the strategies that makes inclusion successful is a commitment to a set of core school values by teachers and administrators (Scruggs & Mastropieri, 1996).…”
Section: Introductionmentioning
confidence: 99%